Propuesta de un sistema de gestión de calidad en la estación de servicios Cooperativa de Transportes Mejía. - De La Cueva Rivera, Mónica Andrea (2021)
Several productive and service organizations are trying to counteract the adverse effects of the worldwide economic depression that has affected all sectors of the economy. Therefore, this project carried out in the Service Station Cooperativa Transporte Mejía was based on the ISO 9001-2015 Standard to develop a proposal for a Quality Management System (QMS) that solves these shortcomings, seeking to consolidate strategies that allow them to increase their competitiveness, improve their service and build customer loyalty. In order to fulfill the objectives set out, a series of activities were carried out using inductive descriptive research as a methodology that allowed the definition of the mission or operational processes, which form part of the value-generating activities carried out employing field research, for the diagnosis and survey of the processes. With the Checklist application, it was possible to verify the non- conformities and the percentages of compliance with the standard resulting in the non-existence of a QMS. So a quality manual was drawn up containing the guidelines that the organization must adopt so that all the activities framed within the respective procedures compile. Simultaneously, documentary support was generated through different formats and records that each essential process must maintain. The results obtained are highly satisfactory, as it was possible to verify the hypothesis, and the proposed management model is entirely applicable and sustainable.